The autobiographic narrative as a ritual in teaching training (Revista Apotheke, 2022)
Liame is a collective textile installation, developed in 2022, with the aim of experiencing autobiographical narratives and reflecting on memories and teaching through sensitive knowledge and textile making. His relational work reverberated some questions: how can the narrative of our memories potentiate practical-reflective actions through textile making? What memories do we carry in our bodies and how can they be re-signified? How does making textiles - handmade - enhance the sharing of memories about teaching? Liame is the result of a Scientific Initiation project (PIBIC/UFPE), developed at the Department of Arts, Federal University of Pernambuco. It permeates the fields of Visual Culture Education, A/r/tography, Textile Art and Memory Studies.
Keywords: Teacher Training; Sensitive Knowledge; A/r/tography; Textile Art; Body and Memory